Optimization of Poly-Si/SiOx Passivated Contacts for Crystalline Silicon Bottom Cells Applications - Julci Ditsougou; Thibaut Desrues; Anne Kaminski; Sébastien Dubois (SiliconPV Conference Proceedings)
In this study we investigate the coupled impacts of poly-Si thickness, dopant activation annealing temperature and hydrogenation on n-TOPCon and p-TOPCon passivated contacts. Their performance is first assessed by Photoconductance Decay (PCD) measurements on symmetrical and asymmetrical cell precursors before being evaluated on cells by I-V characterizations. We show that high-temperature annealing of poly-Si layers is responsible for excessive dopants penetration in the substrate, which can then be limited by the presence of a thicker poly-Si layer. Moreover, these thicker poly-Si layers benefit more from hydrogenation steps, enabling i-Voc of around 720 mV and carrier lifetimes of up to 5 ms on cell precursors. Finally, while increasing the thickness leads to current limitation under AM1.5G (1 Sun) illumination, this limitation is less pronounced under IR illumination. We therefore demonstrate that for tandem applications, the bottom-cell can benefit from a gain in Voc and FF without suffering from a major optical limitation.